Comparison of small group discussions and didactic lectures in pharmacology for medical undergraduate students - Desai, Anupama; Banzal, Neeta (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Conventionally, in most medical colleges, didactic lectures form a major part of teaching, however this method of teaching has many limitations. There has been a paradigm shift in teaching learning methods which now favor enhanced student involvement. Small group discussion (SGD) is one such method which has been frequently compared with didactic lectures. This study aims to compare these two teaching learning methods. Methods: This was a randomized prospective cross sectional, comparative study carried out with 120 second MBBS students of Pharmacology. The students were randomly divided into two groups. Group A was taught by conventional didactic method and group B learnt the same topic by SGD method. For the next topic there was a crossover. After a week students appeared for a test and were asked to fill a 5-point Likert scale perception analysis form. Results: The post-test average scores for didactic lecture were 6.42±2.43 and for SGD were 6.15±2.70 (p value 0.4167). About 88% students agree (50% strongly agree and 38% agree) that SGD is motivating, 85% student agree that SGD is interesting form of learning however 26% student feel that some student dominated in the SGD and 33% student felt more comfortable in lectures. Conclusions: The perception analysis showed that majority of the students found SGD better than didactic lectures in terms of learning, involvement, clearing doubts, increasing self-confidence however analysis of the test scores showed no statistically significant difference amongst the marks obtained after didactic lectures or small group discussion.